2019
DOI: 10.1111/pce.13654
|View full text |Cite
|
Sign up to set email alerts
|

High porosity with tiny pore constrictions and unbending pathways characterize the 3D structure of intervessel pit membranes in angiosperm xylem

Abstract: Pit membranes between xylem vessels play a major role in angiosperm water transport. Yet, their three‐dimensional (3D) structure as fibrous porous media remains unknown, largely due to technical challenges and sample preparation artefacts. Here, we applied a modelling approach based on thickness measurements of fresh and fully shrunken pit membranes of seven species. Pore constrictions were also investigated visually by perfusing fresh material with colloidal gold particles of known sizes. Based on a shrinkage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
108
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 71 publications
(112 citation statements)
references
References 66 publications
1
108
0
Order By: Relevance
“…This might be useful in understanding pit membranes' functional implication in different dehydrated conditions. Our work confirmed previous report that pit membrane constrictions are neither straight nor zigzagging [54,58], although the pores were highly connected ( Figure 2c). In addition, recently developed automatic collector of ultrathin sections scanning electron microscopy (Auto CUTS-SEM) has axial resolution of 100 nm and horizontal resolution of 15 nm [60], which would be satisfying requirements of high resolution for 3D reconstruction of bordered pit membranes from plant materials and further test the modelled intervessel pit membrane structure.…”
Section: Three Dimension Of Intervessel Pit Membrane and Its Functionsupporting
confidence: 92%
See 1 more Smart Citation
“…This might be useful in understanding pit membranes' functional implication in different dehydrated conditions. Our work confirmed previous report that pit membrane constrictions are neither straight nor zigzagging [54,58], although the pores were highly connected ( Figure 2c). In addition, recently developed automatic collector of ultrathin sections scanning electron microscopy (Auto CUTS-SEM) has axial resolution of 100 nm and horizontal resolution of 15 nm [60], which would be satisfying requirements of high resolution for 3D reconstruction of bordered pit membranes from plant materials and further test the modelled intervessel pit membrane structure.…”
Section: Three Dimension Of Intervessel Pit Membrane and Its Functionsupporting
confidence: 92%
“…Given that pit membrane structure is three dimensional, it was recently suggested to use the term constriction size instead of pore size [54]. Although 3D reconstruction of bordered pits has been investigated by various techniques such as resin casting [55], silicone micromolding [56], ptychographic X-ray computed tomography [54], 4Pi and confocal laser scanning microscope [57], the 3D reconstruction of pit membranes demonstrating its porosity and tortuosity, in other words, distribution of constrictions, is so far lacking except for a few simplified models [58]. Hence, more precise modelling work on 3D reconstruction of pit membranes is demanded to further study its morphology and related hydraulic function.…”
Section: Three Dimension Of Intervessel Pit Membrane and Its Functionmentioning
confidence: 99%
“…The interconduit pit membrane thickness (T PM ) was suggested to be more important to embolism resistance than bordered pit area and pit aperture area (Lens et al 2011;Li et al 2016a). Based on a three dimensional view of pit membranes, it has been suggested that pit membrane thickness is related to the number of pore constrictions within a single pore pathway (Kaack et al 2019;Zhang et al 2020). Since the most narrow pore constriction within a pore pathway determines embolism resistance, the likelihood that the smallest pore constriction is very narrow will increase with the number of pore constrictions.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, it is likely that hydraulic bottlenecks show locally highly reduced conduit dimensions, especially with respect to conduit length and width, with a high number of interconduit end walls over a short stretch of xylem tissue. Conduit end walls have been suggested to hold up embolism spreading at least temporarily, with pit membranes functioning as safety valves and preventing further spreading of embolism due to their tiny pores (Zhang et al , 2017(Zhang et al , , 2020Kaack et al , 2019;Johnson et al , 2020). Moreover, narrow and short tracheids or fibriform vessels may be more confined than long and wide vessels, with a small interconduit pit membrane area for air entry.…”
Section: Embolism Spreading Depends On Pre-existing Embolism As Gas Smentioning
confidence: 99%